2014
DOI: 10.1186/s12913-014-0561-x
|View full text |Cite
|
Sign up to set email alerts
|

The association of asthma education centre characteristics on hospitalizations and emergency department visits in Ontario: a population-based study

Abstract: BackgroundInternational guidelines recommend patient education as an essential component of optimal asthma management. Since 1990 hospital-based asthma education centres (AECs) have been established in Ontario, Canada. It is unknown whether patient outcomes are related to the level of services provided.MethodsUsing linked, population-based health administrative and hospital survey data we analyzed a population of patients aged 2 to 55 years with a hospitalization for asthma (N = 12 029) or a high acuity asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 18 Other studies conducted within the last 5 years using different methods have shown similar results. 19 , 20 One study conducted in an inpatient hospital setting demonstrated that solely providing education to the patient resulted in similar benefits with respect to hospitalizations and ED visits. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Other studies conducted within the last 5 years using different methods have shown similar results. 19 , 20 One study conducted in an inpatient hospital setting demonstrated that solely providing education to the patient resulted in similar benefits with respect to hospitalizations and ED visits. 19 …”
Section: Discussionmentioning
confidence: 99%
“…19,20 One study conducted in an inpatient hospital setting demonstrated that solely providing education to the patient resulted in similar benefits with respect to hospitalizations and ED visits. 19 In this present study, most of the parents/caregivers of asthmatic children reported increased knowledge in managing their children's asthma symptoms, triggers, and signs. They further endorsed fewer hospitalizations/ED visits and decreased school absenteeism associated with this education.…”
Section: Discussionmentioning
confidence: 99%
“…During the screening, some studies were excluded because of incomplete data, and others were excluded for their study design23–28; we only included longitudinal studies. Some studies were excluded because the participants of asthma education were not only children 29–31. We just included studies that met our inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies were excluded because the participants of asthma education were not only children. [29][30][31] We just included studies that met our inclusion criteria.…”
Section: Characteristics Of the Excluded Studiesmentioning
confidence: 99%